Pengembangan Media Pembelajaran Digital Berbantuan Quizwhizzer pada Topik Peredaran Darah Manusia di Kelas V SD Negeri 1 Sambijajar - Fatmasari, Winda; Astutik, Leny Suryaning (Universitas Nusantara PGRI Kediri, 2024)
This research aims to develop, test the validity, and test the practicality of assisted digital media quizwhizzer on the topic of human blood circulation. This research uses the ADDIE development model which consists of analysis (Anaylsis), planning (Design), development (Development), Implementation (Implementation), and evaluation (Evaluation). The data collection technique was carried out by testing the validity of the media, materials, learning and distributing questionnaires. The instruments used in this research used media expert validation sheets, material expert validation, learning expert validation, teacher and student questionnaire sheets. The results of the average media validity are 86.5% in the